A2.4 Blood group and hla antibody incompatible kidney transplantation to allow better quality of life in children with end stage renal disease. (4th October 2017) - Stojanovic, J; Adamusiak, A; Chandak, P; Shaw, O; Kessaris, N; Marks, SD; Mamode, N
Abstract : Background: Lack of blood group compatible donors and sensitisation resulting in development of broad spectrum anti-HLA antibodies, is an increasing problem making it difficult for some children with renal disease to undergo transplantation. We have set up the first antibody incompatible transplant programme for children in the UK. Methods: We describe 11 patients who underwent blood group incompatible (ABOi) and 2 who had HLA antibody-incompatible kidney transplantation (referred from other transplant centers). Our well established adult desensitisation protocols were adopted. Results: For 11 ABOi transplants, we used the following protocol: rituximab for titres 1:8 or more; with addition of double plasmapheresis for titres 1:16-1:32 and immunoabsorption if titers >1:64. Death-censored graft survival was 100% and this was comparable with blood group compatible transplants (98%)